Relationships between genetic polymorphisms of IL-1β and rheumatoid arthritis: Genetic polymorphisms of IL-1β in rheumatoid arthritis - Abdulameer, Nawres Adnan (Cellular and Molecular Biology, 2025)
This study aimed to investigate the association between the interleukin-1 beta (IL-1β) gene polymorphism (rs2853550) and the risk of rheumatoid arthritis (RA) in a sample of the Iraqi population. The study included 100 RA patients and 100 healthy controls. Demographic characteristics, including age and gender, were collected and compared between the two groups. The IL-1β (rs2853550) polymorphism was genotyped using the ARMS-PCR method. The distribution of genotypes and alleles of the IL-1β (rs2853550) polymorphism was significantly different between RA patients and healthy controls. The frequency of the heterozygous AG genotype was significantly higher in the patient group compared to the control group (33% vs. 25%, p=0.001). The odds ratio for RA in individuals with the AG genotype was 1.5038 (95% CI: 0.7274-3.1086), indicating that it may be a potential risk factor. Additionally, the frequency of the G allele was significantly higher in RA patients compared to controls (129 vs. 109, p=0.0021), with an odds ratio of 1.5169 (95% CI: 1.0151-2.2667). The present study demonstrates that the IL-1β (rs2853550) polymorphism is associated with an increased risk of rheumatoid arthritis in the Iraqi population. The AG genotype and the G allele of this polymorphism may serve as genetic markers for susceptibility to RA.